Emotional intelligence and motivation in athletes of different modalities - Castro Sánchez, M.; Chacón Cuberos, R.; Zurita Ortega, F.; Puertas Molero, P.; Sánchez Zafra, M.; Ramírez Granizo, I. (Journal of Human Sport & Exercise, 2018)
This research study aims at analysing motivational climate and emotional intelligence in athletes of different categories of sports according to their gender and category of sport practised, on a sample of 372 athletes aged between 18 and 50, evaluated by means of the Perceived Motivational Climate in Sport Questionnaire (PMCSQ-2), the Schutte Self Report Inventory (SSRI) questionnaire on emotional intelligence in sports and a self-registration sheet which measured the variables of gender and category of sports practised. Results show that in the sample of athletes analysed there is a clear orientation towards task, being greater the orientation towards ego in men and standing out orientation towards task in athletes of individual categories with contact. Regarding emotional intelligence, the athletes analysed showed high ratings in the four dimensions, achieving self-emotional management the highest scores, whereas emotion utilisation obtains the lowest grade; no association has been found between emotional intelligence and gender of respondents; as for the category of sports, athletes who practise collective sports with contact are the ones to better handle their emotions. Emotional intelligence correlates directly and significantly with motivational task-oriented climate, but not with ego-oriented climate.